Implementing a maintenance strategic plan using TPM methodology - Correia Pinto, Gustavo Filipe (2021)
The market globalization and worldwide competition has raised the level of demand in the industrial sector. Due to this aggressive competitiveness, some management strategies and tools needed to start to be applied in the industry. For example, maintenance has become increasingly important in the production planning and strategy of some companies. This work focuses on the implementation of a strategic maintenance plan, applied in an industrial context, namely in a company of Clutches and Hydraulic Controls. The Total Productive Maintenance (TPM) methodology application was worked on and implemented at two sections, CNC Lathes and CNC Machining Centers, to focus on eliminating losses due to inefficiencies. In this way, the main problems detected in relation to the cells were eliminated. New autonomous maintenance procedures (AM) and preventive maintenance plans with well-defined schedule were also developed. The results obtained were very positive: there was a decrease of 23% in breakdowns in CNC lathes sector and 38% in CNC machining centers sector. In global terms, there was an increase in the availability of the machines and the Overall Equipment Effectiveness (OEE) of approximately 5%. The implementation procedure and the compromise adopted by the whole company staff and management was the secret to success.